2001
DOI: 10.1046/j.1365-2044.2001.01906.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the disposable Vital View™ laryngoscope

Abstract: The Vital View laryngoscope (Vital Signs, NJ, USA) consists of a plastic disposable blade containing a fibrelight and a non-disposable handle; there is therefore no need to sterilise the blade and no concern about disintegration of the fibrelight. In a random cross-over design, we compared the Vital View laryngoscope with a conventional metal fibrelight laryngoscope (Welch Allyn, NY, USA) in 100 patients. The Vital View laryngoscope produced a brighter field than the metal laryngoscope (p < 0.001), whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…As for Vital View blades, two previous clinical studies did not find any difference with standard blades [20,21]. In a randomized study of 100 patients (crossover design), Asai et al found no significant difference between the plastic blade and the standard Macintosh blades in laryngoscopic view of the glottis [20]. Our earlier observational study also compared Vital View blades and standard Macintosh blades and found similar results [21].…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…As for Vital View blades, two previous clinical studies did not find any difference with standard blades [20,21]. In a randomized study of 100 patients (crossover design), Asai et al found no significant difference between the plastic blade and the standard Macintosh blades in laryngoscopic view of the glottis [20]. Our earlier observational study also compared Vital View blades and standard Macintosh blades and found similar results [21].…”
Section: Discussionsupporting
confidence: 50%
“…Our results were different. As for Vital View blades, two previous clinical studies did not find any difference with standard blades [20,21]. In a randomized study of 100 patients (crossover design), Asai et al found no significant difference between the plastic blade and the standard Macintosh blades in laryngoscopic view of the glottis [20].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Single-use devices could therefore offer a safer practice, provided they perform as well as the re-usable devices they are intended to replace. Asai et al [13] claimed that one single-use plastic laryngoscope blade assessed in 100 patients was easy to use and was not different from a re-usable metal laryngoscope blade. In contrast, Evans and colleagues [14] demonstrated that three plastic single-use blades did not perform as well as metal blades.…”
mentioning
confidence: 99%
“…Disposable adult laryngoscopes have been investigated both in patients [5] and in the laboratory [4,6,7] with varying results. Blade design often changes during the manufacturing process [8,9], and therefore blades from different manufacturers may have different characteristics.…”
mentioning
confidence: 99%